2017
DOI: 10.1209/0295-5075/118/57002
|View full text |Cite
|
Sign up to set email alerts
|

Linearity of the edge states energy spectrum in the 2D topological insulator

Abstract: Linearity of the topological insulator edge state spectrum plays the crucial role for various transport phenomena. The previous studies found that this linearity exists near the spectrum crossing point, but did not determine how perfect the linearity is. The purpose of the present study is to answer this question in various edge states models. We examine Volkov and Pankratov (VP) model [1] for the Dirac Hamiltonian and the model of [2, 3] (BHZ1) for the Bernevig, Hughes and Zhang (BHZ) Hamiltonian [4] with zer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 17 publications
1
23
0
6
Order By: Relevance
“…Often, the edge states in a 2D TI are considered based on the 6-band Bernevig-Hughes-Zhang 15 model with zero boundary conditions on the external border. Less known is the minimal Dirac-like 2-band model by Volkov-Pankratov (VP) 16 first invented for the 3D case and used for the 2D case later [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Often, the edge states in a 2D TI are considered based on the 6-band Bernevig-Hughes-Zhang 15 model with zero boundary conditions on the external border. Less known is the minimal Dirac-like 2-band model by Volkov-Pankratov (VP) 16 first invented for the 3D case and used for the 2D case later [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…First, let us consider the case γ = 0, which corresponds to the isotropic model. Detailed study of the edge states structure within isotropic approximation is presented in [25]. In this case the Hamiltonian (1) is composed of two independent 2×2 blocks.…”
Section: A Isotropic Modelmentioning
confidence: 99%
“…In this case the Hamiltonian (1) is composed of two independent 2×2 blocks. At γ = 0 the Schrödinger equation (2) has an analytical solution, valid for a wide range of k y [20,25] ε (0)…”
Section: A Isotropic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear spectrum of the 2D TI edge states is the main reason of disappearance of the electron correlation energy 13 . In 11 we have studied the linearity of the energy spectrum in the edge states of the 2D topological insulator. We concluded that in two models of the edge states 12 and 1 -3 the linearity is absolute, while in other cases the non-linear corrections are extremely weak.…”
Section: Introductionmentioning
confidence: 99%